What Dress Fits Me Best? Fashion Recommendation on the Clothing Style for Personal Body Shape - Hidayati, Shintami Chusnul; Fu, Jianlong; Cheng, Wen-Huang (ACM International Conference on Multimedia (ACM Multimedia), 2018)
Clothing is an integral part of life. Also, it is always an uneasy task for people to make decisions on what to wear. An essential style tip is to dress for the body shape, i.e., knowing one’s own body shape(e.g., hourglass, rectangle, round and inverted triangle)and selecting the types of clothes that will accentuate the body’s good features. In the literature, although various fashion recommendation systems for clothing items have been developed, none of them had explicitly taken the user’s basic body shape into consideration. In this paper, therefore, we proposed a first framework for learning the compatibility of clothing styles and body shapes from social big data, with the goal to recommend a user about what to wear better in relation to his/her essential body attributes. The experimental results demonstrate the superiority of our proposed approach,leading to a new aspect for research into fashion recommendation.